Cooperation for Sustainable Development: a University Transport Model - Casacchi, Melissa; Rocha, Vivian; Cohen, Marcos; Felipe Guanaes, Luiz (Journal of Sustainability Perspectives, 2021)
The transportation system generally contributes with the largest share of Greenhouse Gases Emissions (GHG) among economic activities, which includes the high level of gas emissions from the transport system in the GHC Inventory from Higher Education Institutions (HEI). Guided by its socio-environmental agenda, the Pontifical Catholic University of Rio de Janeiro (PUC-Rio), has sought to implement integrated programs to encourage the use of alternative transportation in order to mitigate the impacts of urban mobility on the atmosphere since 2010. Free parking and shower facilities for cyclists, as well as pedestrian friendly sites and limited vehicle parking area inside the campus are some of the welcomed interventions implemented by PUC-Rio. In addition, the institution has collaborated technically with the public authorities to enable the arrival of good quality mass transportation to the University neighborhood. Even facing limited mass public transportation in the surroundings of the main campus, PUC-Rio has implemented a series of transportation initiatives that rely on the commitment and partnership of its community (students, professors and staff), who strongly support new solutions for sustainable development and contribute to the improvement of PUC-Rio transportation performance